Irrigação e adubação no cultivo da cebola em ambiente protegido utilizando dados meteorológicos externos - Santos, Ketylen Vieira (2022)
Onion (Allium cepa L.) is one of the most consumed foods and stands out among other vegetables due to its high productive potential, consumption and importance. A technique widely used in onion cultivation is irrigation, mainly in northeastern Brazil, due to climatic characteristics, relief, and air humidity. Combined with irrigation, fertilization is another technique of paramount importance, among the requirements needed by the crop, attention (N) stands out, which has the greatest influence on its production, and potential (K), responsible for several photosynthetic reactions. Since the objective of the study was evaluated, the behavior of the present study was evaluated, the behavior of the study was evaluated, the study of evaluation of the behavior of the evaluation area, using meteorological data, in addition to evaluating the performance of the culture in the different fertilization of roof. DEA at Universidade Federal (UFS) was tested and programmed in blocks, experimental design protected in a factorial scheme of 5 irrigation depth planning methods (Penman-Monteith, Hargreaves-Samani, Camargo, Jensen-Haise and Blanney-Criddle) and different installments of topdressing fertilization covering 15, 30, 45, 60 after transplanting, totaling 20 treatments and 4 measures. After harvest, the following were obtained: total and commercial yield of bulbs, commercial mass of bulbs, non-average water efficiency for total yield and average water use for total yield and pH utilization, solid solids for such, salable solid titration for all solids/total titratable marketable . The top-dressing fertilization installments were statistically insignificant in all variables. The methods of evaluation of the execution blades and the splitting of the execution of the mechanisms do not interfere in the performance for resources of the best cultivar Vale Ouro IPA - 0, being responsible for the execution of the bulbs. of total bulb productivity, commercial water use efficiency for total and commercial productivity and the highest average bulb mass. All treatments provided are considered good results, being recommended by the literature, being alternatives according to the predicted conditions.